Subsidizing Failing Firms: Evidence from Chinese Restaurants - Deng, Yinglu; Lu, Fangzhou; Yu, Jiaheng; Zheng, Hao (Journal of Financial and Quantitative Analysis, 2024)
Abstract Using data on nearly 20,000 restaurants in China during the COVID-19 outbreak, we find evidence that the government-sponsored rent reduction program reduced debt overhang problems. Rent reductions, which averaged 36,000 RMB per restaurant, increase the open rate of restaurants by 3.7%, revenue by 11,000 RMB, and the number of employees by 0.36. Larger restaurants with higher committed costs benefit more from the rent reduction. The stimulus has a positive spillover effect that boosts the revenue of restaurants in the immediate vicinity of subsidized restaurants. The treatment effect varies with organizational structure in a manner consistent with an information frictions hypothesis.